2022
DOI: 10.1021/acsami.2c05296
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectonics of a MOF-in-Nanochannel (HKUST-1/TiO2) Membrane for Multitarget Selective Enrichment and Staged Recovery

Abstract: Enrichment and separation of specific endogenous molecules are essential for disease diagnosis and the pharmaceutical industry. Although many solid sorbents have been developed for target molecule enrichment, simultaneous separation of multitargets is still a challenge for adsorbents. In this study, we develop a multitarget selective sorbent based on a nanochannel membrane prepared by the anodization of a Ti−Cu alloy. The in situ growth of a metal− organic framework (MOF, herein using Cu-based HKUST-1) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The equilibrium data are more consistent with the Langmuir model and exhibit a higher correlating constant (R 2 ), manifesting that BHb could be absorbed by Cu-MOF in a monolayer adsorption manner. Meanwhile, compared to those of previously reported MOF-based BHb absorbents, 19,33,35,[48][49][50] Cu-MOF exhibits superior performance with higher adsorption capacity in the adsorption time of 60 min (Table S2 and Fig. S8, ESI †).…”
Section: Impact Of Phmentioning
confidence: 65%
“…The equilibrium data are more consistent with the Langmuir model and exhibit a higher correlating constant (R 2 ), manifesting that BHb could be absorbed by Cu-MOF in a monolayer adsorption manner. Meanwhile, compared to those of previously reported MOF-based BHb absorbents, 19,33,35,[48][49][50] Cu-MOF exhibits superior performance with higher adsorption capacity in the adsorption time of 60 min (Table S2 and Fig. S8, ESI †).…”
Section: Impact Of Phmentioning
confidence: 65%
“…The growth difference of ZIF-8 in channels with different sizes can be attributed to the limited growth of MOF crystals in the nanoconfined space. 43 It was also observed that the load of ZIF-8 crystals significantly decreased along the channel from the Zn(II) addition side to the 2-methylimidazole (2-Mlm) addition side, resulting from the concentration gradient of precursors (Figure S4). More importantly, only the pore size of ZIF-8/INCE with a pristine AAO size of 28 nm approached several nanometers, which enabled significant nanoconfinement as proven later, indicating that this method may be promising to construct a nanogap for various applications.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Clearly, the smaller the pristine pore size of AAO, the larger the decrease degree of the pore size due to the deposition of MOFs. The growth difference of ZIF-8 in channels with different sizes can be attributed to the limited growth of MOF crystals in the nanoconfined space . It was also observed that the load of ZIF-8 crystals significantly decreased along the channel from the Zn­(II) addition side to the 2-methylimidazole (2-Mlm) addition side, resulting from the concentration gradient of precursors (Figure S4).…”
Section: Resultsmentioning
confidence: 98%
“…These problems ultimately lead to low adsorption performance and environmental pollution, which restrict their practical application. As an alternative strategy, magnetic composites incorporating the metal–organic framework (MOF), , layered double hydroxide (LDH), , and montmorillonite , are also reported for the separation of histidine-rich proteins. Despite the success of the aforementioned strategy in resolving the defects of ligand-based magnetic IMA adsorbents, there is a trade-off between magnetism and adsorption performance.…”
Section: Introductionmentioning
confidence: 99%